Factors Affecting Depression and Anxiety in Diabetic Patients: A Prospective Cohort Study from a Tertiary Care Hospital in Eastern India - Kankana Karpha; Jyotirmoy Biswas; Siddhartha Nath; Arkadeep Dhali (University Library System, University of Pittsburgh, 2022)
• Background: Diabetes is one of the most common chronic diseases in the world and its prevalence in India is rising day by day. Diabetic patients often suffer from depression and anxiety which has a negative impact on patients resulting in non-adherence to medication, rapid disease progression and overall poor prognosis. Aims: The study aims to determine the prevalence of depression and anxiety among diabetic patients and the factors associated with these. Methods: A prospective cohort study was conducted with 305 participants among which 152 were diabetic while 153 were non diabetic patients. Informed written consent was obtained from all study participants. Patients having known psychiatric illnesses, other long standing chronic illnesses, terminally I'll, or on corticosteroids were excluded from the study. Depression and anxiety of the patients was measured through PHQ-9 scale and GAD-7 scale respectively. Factors associated with prevalence of depression and anxiety in the diabetic population was analyzed. Results: In our study 305 participants were recruited among which 153 were non-diabetic (NDM) and 152 were diabetic (DM). The socio-demographic, clinical features and disease characteristics are shown in Table 1. Age and gender distribution among the 2 groups (NDM and DM) were similar (p=0.571). Most of the study participants belonged t age group 45-60 years. Number of widowed participants were significantly higher in the DM group (p=0.009). There was no difference in place of residence, educational status, and income between these groups. Body mass index (p=0.001), fasting blood sugar (p=0.001), and post prandial blood sugar (p=0.001) levels were significantly higher in the DM group compared to the NDM group. Hypertension was also more commonly seen in the DM group (35.9% versus 64.5%, p=0.001). There was a significant difference in depression and anxiety in these groups. In the DM group, 60 (39.5%) and 55 (36.2%) patients had depression and anxiety respectively. In contrast, 19 (12.4%) and 22 (14.4%) patients had depression and anxiety respectively in the NDM group. A subgroup analysis within the DM group (Table 2,3) was done to analyse the predictors of depression and anxiety among the participants. Educational status (OR:0.168, CI:0.050-0.563, p=0.004), marital status (OR:7.334, CI:1.339-40.156, p=0.022), insulin therapy (OR:3.596, CI:1.249-10.351, p=0.018), retinopathy (OR:5.521, CI:2.193- 13.903, p=0.001), hypertension (OR:0.167, CI:0.065-0.431, p=0.001) and ischemic heart disease (OR:5.646, CI:1.923-16.577, p=0.002) were significantly associated with depression. Marital status (OR:6.132, CI:1.214-30.996, p=0.028), retinopathy (OR:7.668, CI:3.120-18.845, p=0.001), neuropathy (OR:3.054, CI:1.239-7.527, p=0.015) and ischemic heart disease (OR:5.356, CI:1.922-14.924, p=0.001) were significantly associated with anxiety. Conclusion: Our study shows depression and anxiety are highly prevalent among diabetic patients. All diabetic patients while seeking clinical contact should be screened for depression and anxiety especially those patients with predisposing risk factors.